Tatarzy polscy – pamięć, przeszłość i etniczność .......... 103 - Warmińska, Katarzyna (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
POLISH TATARS – PAST, MEMORY, AND ETHNICITYThis article explores the interconnections between ethnicity, memory, and the past in the context of the Polish Tatar community. Drawing on theoretical frameworks of collective and cultural memory, it examines how historical narratives are constructed and employed to define ethnic identity. The study analyzes two primary sources of memory transmission: communicative memory, derived from qualitative interviews conducted in the 1990s and early 2000s, and cultural memory, as represented in the ethnic periodical “Przegląd Tatarski”. The findings highlight how Polish Tatars selectively recall historical events, emphasizing their military contributions and long-standing loyalty to Poland, while also negotiating their distinct religious and cultural heritage. The analysis suggests that memory functions as a key mechanism in maintaining ethnic boundaries and legitimizing the group’s presence within the national historical discourse. The research contributes to broader discussions on minority identity formation and the role of memory institutions in shaping ethnic belonging.